PENGELOLAAN KEUANGAN BADAN USAHA MILIK DESA (BUMDes) STUDI KASUS PADA BUMDes KEMBANG DESA KEMIRI KECAMATAN PANTI - Maya Ilma Navi’ah,; Norita Citra Yuliarti,; Elok Fitriya, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research aims to find out how financial management carried out by BUMDes Kembang, Kemiri Village, Panti District inorder to optimize the potential of the village. The research includes descriptive research with a qualitative approach. The results of this study show that the financial management carried out by BUMDes Kembang is carried out cooperatively and participatively, all BUMDes administrators participate in the process of managing BUMDes operations although there are obstacles that sometimes occur don’t make it an obstacle not to participate in the development of BUMDes. In its financial management, BUMDes Kembang carries out the planning, implementation, management, reporting and accountability stages. However, in the implementation and administration stage of BUMDes Kembang it is still not appropriate. At the implementation stage, the recording is still simple and has not yet arrived in the general ledger. Administration is carrid out when there is assistance from outside parties.